Public engagement: Talking science to laypersons as perceived by postgraduate students in Jordan - ABDALLAH KHATAYBEH (Journal of Advanced Research in Social Sciences and Humanities, 2018)
Aim: This research sought to understand how and why postgraduate students in Jordan viewed the importance of involving non-laypersons in their research.Method: Twelve hundred-eight graduate students from Yarmouk University were randomly chosen for this study. Twenty-four items were taken from a questionnaire with a Likert scale of 1-5.Findings: Respondents agreed that communicating with and involving the public was important and that doing so would benefit their everyday lives and the proper application of technology. In the end, scientists need to be able to convey their findings to the general public.Implications/Novel Contribution: Communication facilitates the spread of information and its subsequent application. How cooperation can be encouraged is explored in detail in the report. The findings will aid non-laypersons in training and communication.